Language Game dan Pengembangan Konsep Kognitifpragmakritis - Fidiyanti, Murni; Suhartono; Sodiq, Syamsul (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This article concerned to the integration of language game concept by Ludwig Wittgenstein with the others sub field of linguistics; Cognitive Linguistics, Pragmatics and Critical Discourse Analysis. Language Game is the basic of the appearance of sub fields of linguistics that relate to causality approach. Without causality approach, language is just the sound without meaning. This point makes some sub field of linguistics such as Cognitive Linguistics, Pragmatics, Critical Discourse Analysis appearance to analyze the use of language in human life. Language game and the development of a Critical Cognitive-Pragmatics concept can be seen from some dimensions of philosophy view. First is ontology dimension. The meaning essence of language game is the use of language in human life which is spontaneous, complex and unlimited. These characteristics are the result of the relation of human being with themselves, society, nature and God. By this concept, a Critical Cognitive-Pragmatics concerned on the description of language game. The second is axiological dimension. It is about values and evaluation of language use in any contexts. Values and evaluation refer to the meaning of words or utterances based on context in language game. The third is epistemological dimension. It refers to the use of language in social interaction for understanding and forming the reality. This frame reveals the use of language that relate to the reality, perception and power in society.